Biosynthesis of flavan 3-ols by leucoanthocyanidin 4-reductases and anthocyanidin reductases in leaves of grape (Vitis vinifera L.), apple (Malus x domestica Borkh.) and other crops - Pfeiffer, Judith (Plant physiology and biochemistry : PPB, 2006)
Catechin and epicatechin biosyntheses were studied of grape (Vitis vinifera L.), apple (Malus x domestica Borkh.) and other crop leaves, since these monomers and the derived proanthocyanidins are important disease resistance factors. Grape and apple leucoanthocyanidin 4-reductase (LAR; EC 1.17.1.3) enzymes were characterized on basis of plant and recombinant enzymes. In case of grape, two LAR cDNAs were cloned by assembling available EST sequences. Grape and apple leaf anthocyanidin reductase (ANR; EC 1.3.1.77) cDNAs were also obtained and the respective plant and recombinant enzymes were characterized. Despite general low substrate specificity, within the respective flavonoid biosyntheses of grape and apple leaves, both enzyme types deliver differently hydroxylated catechins and epicatechins, due to substrate availability in vivo. Furthermore, for LAR enzymes conversion of 3-deoxyleucocyanidin was shown. Beside relevance for plant protection, this restricts the number of possible reaction mechanisms of LAR. ANR enzyme activity was demonstrated for a number of other crop plants and its correlation with (-)-epicatechin and obvious competition with UDP-glycosyl:flavonoid-3-O-glycosyltransferases was considered